Price Manipulation by Dissemination of Rumors: Evidence from the Indonesian Stock Market - Wirama, Dewa Gede; Wiksuana, I Gusti Bagus; Mohd-Sanusi, Zuraidah; Kazemian, Soheil (International Journal of Economics and Financial Issues, 2017)
This study examines stock market reactions to the publication of rumors in Indonesia market. Using 672 market rumors published in the electronic version of the Investor Daily Indonesia newspaper for the period starting from 3 August 2007 to 31 December 2008, this research shows that market rumors were intentionally published by sellers to attract buyers. They are a part of a manipulation scheme that is intended to enable the manipulator to sell at higher prices stocks that they previously accumulated at lower prices. The findings of this research indicate that the stock market is not fully efficient as prices could be manipulated by rumors. Consequently, the existence of market rumors should be considered in timing the buy and sell decision. Regulators might also want to put into effect stronger regulation against spreading false information to protect the small and usually less informed investors. Keywords: rumor, market manipulation, abnormal return, investment decision, regulation. JEL Classifications: GO1, G14, G15